5
$\begingroup$

A begins by throwing a dice until he gets $6$, then B does the same thing.
What is the probability that A throws more times than B?

I try to solve it, but I got 2 different answers:
1. We mark: $X=$How many times A throws, $Y$=How many times B throws. $$P(X>n|Y=n)=\frac{P(X>n)\cdot P(Y=n)}{P(Y=n)}=P(X>n)\\ \sum_{k=n}^\infty\left(\frac56\right)^{k-1}\cdot \left(\frac16\right)=\left(\frac65\right)^{1-n}=\left(\frac56\right)^{n-1}$$ 2. The second way is: We can say that "B throw less times than A", so let's assume that A throws the dice $n$ times. So: $$P(Y<n)=\sum_{k=1}^{n-1}\left(\frac56\right)^{k-1}\cdot \left(\frac16\right)=1-\left(\frac56\right)^{n}$$

They are opposite, and I don't know which one of them is correct or both of them are incorrect..

Please help with this.
Thank you!

$\endgroup$
  • $\begingroup$ A more challenging question would be to compute the probability of B getting a 6 6(two consecutive sixes) sooner than A getting a 5 6. $\endgroup$ – gar Mar 30 '14 at 13:55
10
$\begingroup$

A and B throwing dice are two independent events, so you need to multiply them and evaluate an infinite sum of geometric series.

$\displaystyle P(X>n)=\left(\dfrac{5}{6}\right)^n\\\\ P(Y=n)=\left(\dfrac{5}{6}\right)^{n-1}\cdot \left(\dfrac{1}{6}\right) $

and the required probability:

$\displaystyle \mathbb{P}=\sum_{n\ge 1} P(X>n)\cdot P(Y=n)=\dfrac{5}{11} \approx 0.4545 $

$\endgroup$
8
$\begingroup$

In order to avoid the double sum, note that the problem is symmetric. The probability that A throws more times than B is equal to the probability that B throws more times than A; call this probability $p$.

Now let's calculate the probability that both A and B throw the same number of times; this will be $1-2p$. This is

$P(A=B) = \sum_k P(A=k, B=k) = \sum_k P(A=k) P(B=k) = \sum_k P(A=k)^2$

and we can write out the sum explicilty as

$\sum_{k=1}^\infty ((5/6)^{k-1} (1/6))^2$

or, after some simplification,

$(1/36) \sum_{j=0}^\infty (25/36)^j$.

Summing the series, this is $1/11$. So $1-2p = 1/11$ and therefore $p = 5/11$.

$\endgroup$
5
$\begingroup$

enter image description here I am a new user and I really need 5 points. Hope this helps.

$\endgroup$
4
$\begingroup$

As has been pointed out, if we find the probability $p$ of a tie, we will know the answer. The probability of a tie is readily found by summing an infinite series. We calculate it another way.

A tie can happen in two ways: (i) both A and B get a $6$ on their first throw or (ii) neither does, but they ultimately tie. The probability of (1) is $\frac{1}{36}$. The probability of (ii) is $\frac{25}{36}p$. Thus $$p=\frac{1}{36}+\frac{25}{36}p.$$ Solve this linear equation for $p$. We get $p=\frac{1}{11}$.

$\endgroup$
2
$\begingroup$

Note that if A doesn't get a 6 first roll (probability 5/6), then the probability of B getting a 6 first is the same as the probability of A getting a 6 first was before the first roll.

If $p_A $ is the probability of A getting a 6 first, $p_B$, of B first. Then we have

$$p_A + p_B = 1\text{, and }\;p_B = \dfrac{5}{6} p_A$$

So

$$\dfrac{6}{5} p_B + p_B = 1$$

hence

$$p_B = \dfrac{5}{11}$$

$\endgroup$
1
$\begingroup$

You need to sum over $n$ and multiply by the probability that $Y$ throws $n$.

Let $X=$number of throws until A gets a 6, $Y$=number of throws until B gets a 6 Then $A$ wins if \begin{align*} &\sum_{n=1}^{\infty} P(X>n|Y=n)\cdot P(Y=n) \\ &=\sum_{n=1}^{\infty}\frac{P(X>n)\cdot P(Y=n)}{P(Y=n)} \cdot P(Y=n) =\sum_{n=1}^{\infty} P(X>n) \cdot P(Y=n)\\ &= \sum_{n=1}^{\infty} \left(\left(\frac{5}{6}\right)^{n}\left( \frac{1}{6}\right) + \left(\frac{5}{6}\right)^{n+1}\left( \frac{1}{6}\right) +\ldots\right) \cdot \left(\frac{5}{6}\right)^{n-1}\left( \frac{1}{6}\right)\\ &=\frac{5}{11} \end{align*}

$\endgroup$
0
$\begingroup$

To find the probability that A throws more times than B, we need to sum the probabilities that A throws two or more times given that B throws once, A throws three or more times given that B throws twice and so on.

So we need to evaluate

$\sum_{k=1}^{\infty}P(A_{throws} > k,B_{throws}=k)$

Now for B throwing once, and A throwing two or more times, we have as probability (using the sum to infinity of a geometric progression)

$\large \frac{1}{6}\times\sum_{k=1}^{\infty}\left(\frac{5}{6}\right)^k\left(\frac{1}{6}\right)=\left(\frac{1}{6}\right)^2\left(\frac{\frac{5}{6}}{1-\frac{5}{6}}\right)=\frac{1}{6}\left(\frac{5}{6}\right)$

For B throwing twice, and A throwing three or more times, we have as probability (using the sum to infinity of a geometric progression as before)

$\large\left(\frac{5}{6}\right) \frac{1}{6}\times\sum_{k=2}^{\infty}\left(\frac{5}{6}\right)^k\left(\frac{1}{6}\right)=\left(\frac{5}{6}\right)\left(\frac{1}{6}\right)^2\left(\frac{\left(\frac{5}{6}\right)^2}{1-\frac{5}{6}}\right)=\frac{1}{6}\left(\frac{5}{6}\right)^3$

For B throwing three times, and A four or more times we have

$\large\left(\frac{5}{6}\right)^2 \frac{1}{6}\times\sum_{k=3}^{\infty}\left(\frac{5}{6}\right)^k\left(\frac{1}{6}\right)=\left(\frac{5}{6}\right)^2\left(\frac{1}{6}\right)^2\left(\frac{\left(\frac{5}{6}\right)^3}{1-\frac{5}{6}}\right)=\frac{1}{6}\left(\frac{5}{6}\right)^5$

Generalising for B throwing $m$ times and A throwing $m+1$ or more times, the probability is given by

$\large \frac{1}{6}\left(\frac{5}{6}\right)^{2m-1}$

Thus, the probability that A throws more times than B is given by the following scaled sum to infinity of a geometric progression with ratio $\left(\frac{5}{6}\right)^2$

$\large \sum_{k=1}^{\infty}P(A_{throws}>k,B_{throws}=k)=\frac{1}{6}\sum_{k=1}^{\infty}\left(\frac{5}{6}\right)^{2k-1}=\frac{1}{6}\frac{\frac{5}{6}}{1-\left(\frac{5}{6}\right)^2}=\frac{5}{11}$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.